2021
DOI: 10.1039/d1cp00979f
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting the EXAFS obtained under air and H2 environments to reveal details of the surface structure of Pt–Sn nanoparticles

Abstract: Understanding the surface structure of bimetallic nanoparticles is crucial for heterogeneous catalysis. Although surface contraction has been established in monometallic systems, less is known for bimetallic systems, especially of nanoparticles....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…The white line of LAS2 corresponding to peak E is shifted to a lower energy than that after heat treatment, while the peaks of the other samples are similar to that of the reference t‐SnO 2 . This indicates that heat treatment causes a valence change from Sn 2+ to Sn 4+ 30,31 …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The white line of LAS2 corresponding to peak E is shifted to a lower energy than that after heat treatment, while the peaks of the other samples are similar to that of the reference t‐SnO 2 . This indicates that heat treatment causes a valence change from Sn 2+ to Sn 4+ 30,31 …”
Section: Resultsmentioning
confidence: 98%
“…This indicates that heat treatment causes a valence change from Sn 2+ to Sn 4+ . 30,31 25 The crystal structure of ZrSnO 4 for the simulation was referred to NIMS MatNavi number: 4295349472_1_2. the bonding distance decreases with increasing heattreatment temperature for crystallization, as indicated by the dashed line in Figure 10(B).…”
Section: Resultsmentioning
confidence: 99%
“…The similarity in the expected bond lengths for Pt-Pt (2.75-2.81 Å) and Pt-Sn (2.78-2.83 Å) causes difficulty in distinguishing bonds from the Pt L 3 -edge perspective. [39] This challenge is reflected in a disagreement reported for the Pt-Sn and Pt-Pt bond lengths [40,41] with studies assigning Pt-Sn and Pt-Pt radial distances differently with close values. While we perform the analysis on both edges; with shared physical constraints (detailed in the Supplementary Information); we focused our analysis on Sn K-edge after catalyst reduction using the minority element (Sn) (details described in the Supplementary Information).…”
Section: Structural Characterization Of Synthesized Nanocrystalsmentioning
confidence: 99%
“…22,23 Hydrogen addition has also been found to cause restructuring of PtSn particles and increase Pt−Sn interactions. 24 The resistance of Pt and PtSn clusters and nanoparticles to sintering can be improved by encapsulating them within the pores of a zeolite. Of particular interest has been the idea of using dealuminated β zeolite (DeAlBEA) containing non-noble metal sites (Zn, Sn, etc.).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The most extensively investigated catalysts for PDH are supported Pt and bimetallic PtSn. , Previous studies have found that Pt is quite active for PDH but suffers from deactivation and poor selectivity. However, the activity, propene selectivity, and stability of Pt improve with decreasing particle size and are best for isolated Pt atoms. , Both experimental and theoretical studies have shown that the addition of Sn increases the dispersion of Pt, enhances the rates of PDH, and reduces the rate of coke formation. PtSn catalysts contain a variety of structures and Pt/Sn ratios, e.g., Pt particles, PtSn bimetallic alloys (e.g., Pt 3 Sn, PtSn), small, supported PtSn bimetallic particles, and isolated Pt atoms interacting with Sn, the nature of these structures depending on the catalyst preparation procedure, Pt/Sn ratios, and support composition. Pt 3 Sn is often cited as the most active bulk alloy, although PtSn has also been shown to be active . The addition of hydrogen to the feed propane has been reported to enhance the rate of PDH by up to 4-fold, with an optimum propane-to-hydrogen ratio of 1:1. , Hydrogen addition also decreases the deactivation of PtSn catalysts due to coking by removal of coke precursors through the reaction with atomically adsorbed hydrogen, an interpretation supported by theoretical studies. , Hydrogen addition has also been found to cause restructuring of PtSn particles and increase Pt–Sn interactions. …”
Section: Introductionmentioning
confidence: 99%